2013
DOI: 10.1002/jmv.23536
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter evaluation of the elecsys® anti‐HCV II assay for the diagnosis of hepatitis C virus infection

Abstract: Routine screening of patients at risk of hepatitis C virus (HCV) infection has become a priority given recent improvements in therapeutic options and the asymptomatic nature of most chronic infections. The aim of this study was to evaluate the performance of the Elecsys® Anti-HCV II assay, a new qualitative antibody immunoassay, compared with currently available assays, and assess its suitability for routine diagnostic testing. The sensitivity of the Elecsys® Anti-HCV II, ARCHITECT® Anti-HCV, AxSYM® HCV 3.0, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
(20 reference statements)
1
20
0
1
Order By: Relevance
“…A number of previous studies have reported the threshold S/Co ratios for a variety of anti-HCV IgG assays [6,7,[9][10][11], and the CDC has published a list of S/Co ratios predictive of a true positive result ≥ 95% of the time for six different immunoassays [1,2]. The Elecsys Anti-HCV II immunoassay was reported to have superior performance compared to several other commercially available assays [8,12]. A previous study has shown that the Elecsys Anti-HCV II immunoassay was sensible, specific, and suitable for the detection of anti-HCV antibodies [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of previous studies have reported the threshold S/Co ratios for a variety of anti-HCV IgG assays [6,7,[9][10][11], and the CDC has published a list of S/Co ratios predictive of a true positive result ≥ 95% of the time for six different immunoassays [1,2]. The Elecsys Anti-HCV II immunoassay was reported to have superior performance compared to several other commercially available assays [8,12]. A previous study has shown that the Elecsys Anti-HCV II immunoassay was sensible, specific, and suitable for the detection of anti-HCV antibodies [8].…”
Section: Discussionmentioning
confidence: 99%
“…The Elecsys Anti-HCV II immunoassay was reported to have superior performance compared to several other commercially available assays [8,12]. A previous study has shown that the Elecsys Anti-HCV II immunoassay was sensible, specific, and suitable for the detection of anti-HCV antibodies [8]. The high sensitivity of the assay makes it suitable for the screening of blood donors [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBs Ag and HCV Ab+ were detected by NIBSC 00/588; WHO 2nd International Standard for HBsAg, subtype adw2, genotype A; UI/mL with 99.9% specificity and 99.8% sensitivity (Muhlbacher et al, 2008) and hepatitis C antibody (Anti-HCV) by cobas e 411 analyzer, Elecsys® 2010 analyzer: 4.2 -5.2 % with100.0% sensitivity and 99.6% hospitalized patients clinical specificity (Esteban, 2013 ) …”
Section: Laboratory Methodsmentioning
confidence: 99%
“…The initial test to screen for HCV infection is based on the use of third-generation enzyme immunoassays (EIA) to detect anti-HCV antibodies against recombinant HCV proteins of the Core, NS3, NS4, and NS5 regions (7) in plasma or serum. Serologic assays cannot discriminate acute from chronic or resolved infection (8), so that EIA positives require the detection of HCV RNA to define active HCV infection.…”
Section: Introductionmentioning
confidence: 99%